Cellular and molecular mechanisms of IMMunE dysfunction and Recovery from SEpsis-related critical illness in adults: An observational cohort study (IMMERSE) protocol paper. (August 2022) - Fish, Matthew; Arkless, Kate; Jennings, Aislinn; Wilson, Julie; Carter, Michael J; Arbane, Gill; Campos, Sara; Novellas, Neus; Wester, Rianne; Petrov, Nedyalko; Niazi, Umar; Sanderson, Barney; et al.
Sepsis is a common illness. Immune responses are considered major drivers of sepsis illness and outcomes. However, there are no proven immunomodulator therapies in sepsis. We hypothesised that in-depth characterisation of sepsis-specific immune trajectory may inform immunomodulation in sepsis-related critical illness. We describe the protocol of the IMMERSE study to address this hypothesis. We include critically ill sepsis patients without documented immune comorbidity and age–sex matched cardiac surgical patients as controls. We plan to perform an in-depth biological characterisation of innate and adaptive immune systems, platelet function, humoral components and transcriptional determinants of the immune system responses in sepsis. This will be done at pre-specified time points during their critical illness to generate an illness trajectory. The sample size for each biological assessment is different and is described in detail. In summary, the overall aim of the IMMERSE study is to increase the granularity of longitudinal immunology model of sepsis to inform future immunomodulation trials.